Predictive factors of quality of life in temporal and extratemporal lobe epilepsy: association with affective temperament profiles and psychiatric comorbidities - Basaran, Sehnaz; Tas, Halil İbrahim (Arquivos de Neuro-Psiquiatria, 2021)
Background: Investigating predictive factors of reduced quality of life (QOL) of patients and their association with focal epilepsy can improve management and treatment strategies. Objective: This study aimed to investigate the relationship between affective temperaments, depression, anxiety, disease characteristics, and QOL and to explore the predictors of QOL in patients with temporal lobe epilepsy (TLE) and extratemporal lobe epilepsy (ETLE). Methods: A total of 50 patients with TLE, 51 patients with ETLE, and 70 controls were enrolled. Affective temperaments were evaluated using the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego-Autoquestionnaire (TEMPS-A). QOL was assessed by the Short-Form Health Survey (SF-36). Beck Depression Inventory and Beck Anxiety Inventory were used to explore depression and anxiety severity, respectively. Results: Compared with the controls, patients with TLE and ETLE had significantly higher scores on all TEMPS-A scales, except on hyperthymic temperament. All the SF-36 subscale scores were lower in the TLE and ETLE groups. Linear regression analysis revealed that depressive symptoms, anxiety, depressive and irritable temperament, and seizure frequency were significant predictors of QOL in TLE. Patients with ETLE with temperamental disturbances, depressive symptoms, and polytherapy had a poorer QOL. Conclusions: Affective temperaments, psychiatric disorders, and clinical factors may predict impaired QOL in patients with TLE and ETLE. Further studies are needed to identify predictors of QOL in various epilepsy subtypes.
Keywords: Epilepsy; Temperaments; Quality of Life; Temporal Lobe; Epilepsy, Temporal Lobe